Memahami penggunaan kontinu mobile wallet di Indonesia: Integrasi Technology Acceptance Model dengan interaksi sosial - Sitorus, Hotna Marina; Wibisono, Yogi Yusuf; Kurnia, Felick (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
While the use of mobile wallets in Indonesia has increased, the country remains behind other ASEAN nations, notably Thailand and Vietnam. This study seeks to investigate the factors influencing Indonesians’ intention to continue using mobile wallets by incorporating the Technology Acceptance Model with social interactions, particularly social connectedness and social influence. This study aims to offer a theoretical contribution by exploring the role of the social interactions, specifically social connectedness, which has not been previously investigated in mobile wallets adoption research. The data collection process involved surveying mobile wallet users in key urban areas in Indonesia, yielding a total of 228 data. The research model underwent testing through the PLS-SEM methodology, revealing that the intention of Indonesians to continue utilizing mobile wallets is influenced by ease of use, benefits, and social connectedness. This study also presents recommendations for relevant stakeholders to persuade users to maintain their use of mobile wallets.